REPRESENTASI KECANTIKAN PEREMPUAN DALAM IKLAN WARDAH MELALUI "VIDEO MUSIK NYAMANKU BAHAGIAKU" ANALISIS SEMIOTIKA ROLAND BARTHES - Marselina Karunia Sukacita (2023)
Beauty is a term that is closely related to one's appearance. Every woman has her own beauty. The idea that beautiful women are perfect is one of the causes of the beauty standard phenomenon, women's beauty is seen more from the outside than from the inside. This study aims to discuss and interpret the beauty of women contained in Wardah's advertisements through the "Musik Video Nyamanku Bahagiaku". The method used is descriptive qualitative using primary data sources and secondary data. Data collection techniques by means of observation and documentation, as well as data analysis techniques using Roland Barthes' semiotic analysis. The final results of this study indicate that the representation of women's beauty shown in Wardah advertisements through the video clip "Nyamanku Bahagiaku" is a woman with clean white skin, a sharp nose, and a slender body which is in accordance with current beauty standards. However, the beauty displayed by Wardah is not only physical beauty or outer beauty but also beauty from within a woman or inner beauty. Where advertising is a forum that can influence society, therefore Wardah displays the true meaning of beauty so that women can be inspired.